2005
DOI: 10.1021/ja054171l
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid-Catalyzed Allylboration:  Short and Stereodivergent Synthesis of All Four Eupomatilone Diastereomers with Crystallographic Assignments

Abstract: This study describes a novel Brønsted acid-catalyzed allylboration method suitable for the most difficult, electronically deactivated allylboronate and aldehyde substrates. This method circumvents the use of metal ions, and rather employs a simple and cheap catalyst, triflic acid. Its usefulness as a complementary allylboration variant was demonstrated with a four-step, stereodivergent synthesis of all four diastereomers of eupomatilone-6 from a single allylboronate. A thorough proof of stereochemistry support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…The focus of this report is the compatibility of diazoalkanes with Brønsted acid catalysts. However, advances in the understanding of azide compatibility with Brønsted acids, [42] as well as others, [18] suggest that numerous innovative opportunities will soon come to light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of this report is the compatibility of diazoalkanes with Brønsted acid catalysts. However, advances in the understanding of azide compatibility with Brønsted acids, [42] as well as others, [18] suggest that numerous innovative opportunities will soon come to light.…”
Section: Discussionmentioning
confidence: 99%
“…Although the focus here is the diazoalkane, the rather surprising compatibility of strong Brønsted acids with other nucleophiles has also been discovered. [18,19] Even though the merits of organocatalysts that function solely by hydrogen bonding are readily accepted, [20] an understanding of the factors that affect the rate of proton transfer to the diazoalkane to form a C À H bond will be directly related to the pace at which new Brønsted acid promoted reactions will be developed. A diverse group of investigators have collectively identified a range of useful carbon-carbon bond-forming reactions amenable to Brønsted acid catalysis in this first five year period (2005)(2006)(2007)(2008)(2009).…”
Section: Brønsted Acid "Compatibility" With Diazo Compoundsmentioning
confidence: 99%
“…In 2005, the Hall group found that strong Br ø nsted acids, such as trifl ic acid, could catalyze the addition of allylboronates to aldehydes [45] . Because, in general, chiral Lewis acid -catalyzed allylation to aldehydes led only to low levels of enantioselection, they demonstrated that chiral LBA catalyzes the asymmetric allylation and crotylation to various aldehydes to afford products in excellent yields and moderate to good enantioselectivity [46,47] .…”
Section: Omementioning
confidence: 99%
“…Dabei standen vor allem Diazoalkane im Zentrum des Interesses, doch auch für andere Nucleophile wurde eine überraschende Vereinbarkeit mit starken Brønsted-Säuren festgestellt. [18,19] Die Verdienste der Organokatalysatoren, die ihre Wirkung ausschließlich über Wasserstoffbrücken entfalten, sind inzwischen weithin anerkannt.…”
Section: Vereinbarkeit Von Brønsted-säuren Mit Diazoverbindungenunclassified